The hidden continuum of HIVassociated cardiomyopathy: A focussed review with case reports - Robbertse, Pieter-Paul; Doubell, Anton; Nachega, Jean; Herbst, Philip (SA Heart Journal, 2021)
HIV-associated cardiomyopathy (HIVAC) is a poorly understood group of diseases with a poor prognosis once ventricular dysfunction is present. Cardiovascular magnetic resonance has revealed a previously unappreciated burden of asymptomatic myocardial abnormalities in people living with HIV, including abnormalities already present at the time of HIV diagnosis. These abnormalities include thickened, inflamed ventricles that bear resemblance to cases of symptomatic HIVAC that are reported on in this article. Our understanding and the significance of asymptomatic HIV-associated myocardial pathology will be explored as early disease on a continuum towards more advanced cardiomyopathy. The need for prospective research in persons naïve to anti-retroviral therapy is emphasised as it may provide key findings to better understand this elusive disease process.